Discovery and mass measurement of the hot, transiting, Earth-sized planet, GJ 3929 b - Kemmer, Jonas; Dreizler, S.; Kossakowski, Diana; Stock, Stephan; Quirrenbach, Andreas; Caballero, J. A.; Amado, P. J.; Collins, K. A.; Espinoza, N.; Herrero, E.; Jenkins, J. M.; Latham, D. W.; et al. (Astronomy and astrophysics, 2022)
We report the discovery of GJ 3929 b, a hot Earth-sized planet orbiting the nearby M3.5 V dwarf star, GJ 3929 (G 180-18, TOI-2013). Joint modelling of photometric observations from TESS sectors 24 and 25 together with 73 spectroscopic observations from CARMENES and follow-up transit observations from SAINT-EX, LCOGT, and OSN yields a planet radius of Rb = 1.150 ± 0.040 R⊕, a mass of Mb = 1.21 ± 0.42 M⊕, and an orbital period of Pb = 2.6162745 ± 0.0000030 d. The resulting density of ρb = 4.4 ± 1.6 g cm−3 is compatible with the Earth’s mean density of about 5.5 g cm−3. Due to the apparent brightness of the host star (J = 8.7 mag) and its small size, GJ 3929 b is a promising target for atmospheric characterisation with the JWST. Additionally, the radial velocity data show evidence for another planet candidate with P[c] = 14.303 ± 0.035 d, which is likely unrelated to the stellar rotation period, Prot = 122 ± 13 d, which we determined from archival HATNet and ASAS-SN photometry combined with newly obtained TJO data.